The impact of non‐pharmaceutical interventions on COVID‐19 cases in South Australia and Victoria - Adriana Milazzo; Lynne Giles; Natalie Parent; Sophie McCarthy; Caroline Laurence (Elsevier, 2022)
Abstract Objective: To assess the impact of different non‐pharmaceutical interventions (NPIs) on COVID‐19 cases across Victoria and South Australia. Methods: Poisson regression models were fit to examine the effect of NPIs on weekly COVID‐19 case numbers. Results: Mask‐wearing in Victoria had a pronounced lag effect of two weeks with an incidence rate ratio (IRR) of 0.27 (95%CI 0.26-0.29). Similarly, the effect of border closure (IRR 0.18; 95%CI 0.14-0.22) in South Australia and lockdown (IRR 0.88; 95%CI 0.86-0.91) in Victoria showed a decrease in incidence two weeks after the introduction of these interventions. Conclusions: With the ongoing COVID‐19 pandemic, varying levels of vaccination coverage rates and threats from variants of concern, NPIs are likely to remain in place. It is thus important to validate the effectiveness and timing of different interventions for disease control, as those that are more restrictive such as border control and lockdown can have an enormous impact on society. Implications for public health: Low case numbers and deaths in Australia's first wave of COVID‐19 are thought to be due to the timely use of interventions. The observed two‐week lag effect associated with a decrease in incidence provides justification for early implementation of NPIs for COVID‐19 management and future pandemics.